Fibrous drugs for curing various common health problems - Dakhara, Sanjay L.; Anajwala, Chetan C.; Selote, Vidula S. (Pharmacognosy Reviews, 2012)
In the past 50 years, dietary fiber has become an increasingly significant area of nutritional focus, debate, and research. Advances in food production practices have resulted in more refined foods being available and consumed across the world and particularly in developed nations such as the US. While refined foods are typically more palatable to consumers, the content of dietary fiber is greatly reduced. Currently, many diseases are believed to be associated with a lack of dietary fiber intake and, furthermore, significant health benefits are thought possible via increased consumption of many dietary fibers. There is no well accepted definition for dietary fiber, but most of the references mention the inability of humans to fully digest fibers; most others say about fibers being made of various monomer units of variable length and some mention plant origin. There are many raw materials/ingredients that can increase the fiber content in foods, each with its own set of functional and sensory characteristics, including acacia gum, beta-glucan, cellulose, chitin/chitosan, corn bran, corn fiber, inulin, oat bran/oat fiber, pea fiber, pectin, polydextrose, psyllium, resistant starch, rice bran, soy fibers, wheat bran, and wheat fiber. All these fibers are unique in their functional capability for treatment of number of diseases.
Keywords: Dietary fiber; inulin; psyllium; soy fibers; wheat bran